Adult Hemophiliacs in Pakistan: Health-Related Quality of Life and Psychological Aspects - Yaqoob, Eesha; Mushahid, Zonaira; Asif, Muhammad Asad; Ishfaq, Muhammad; Sabah, Maheen; Waseem, Mishal (Journal of Rawalpindi Medical College, 2023)
Introduction: Coagulation factor VIII (FVIII) (in hemophilia A) or IX (FIX) (in hemophilia B) deficiency associated with the X chromosome is the primary cause of hemophilia. Bleeding carried on by hemophilia can have an impact on a patient’s mental health and quality of life. Recurrent bleeds in their muscles and joints cause hemophilia patients to experience constant pain. Certain variables, such as depression brought on by low self-esteem in comparison to "normal" siblings and peers, may have an impact on hemophilia patients. Objective: The goal of this investigation is to assess how psychological factors and pain affect adult hemophiliac patients’ well-being. Materials and Methods: On 102 hemophiliacs, a cross-sectional study was done. Data were gathered using visual analogue scales for pain, depression anxiety stress assessments, and quality of life questionnaires specific to hemophilia. Regression analysis, analysis of covariance, and correlation coefficients were used to analyze the data. Results: According to the findings, 70.8% of hemophiliac patients felt pain on the research day. Patients with hemophilia had an average HRQoL score of 50.08 (standard deviation: 18.49). Additionally, stress, worry, and mild to serious depression were present in 45.7 %, 63.5% and 58.3% of the patients, respectively. Additionally, a substantial correlation between HRQoL and sadness, anxiety, and pain intensity were found. The study variables were able to explain 47% of changes in HRQOL in the regression model, with depression and pain intensity serving as important predictors. Conclusion: To enhance the psychosocial health and quality of life of patients, emphasis should be given to these factors.